Analysis of the Role of ERP Systems in Business Process Integrity - Indah Aryani; Rifki Akmal Tanjung; Niken Rahmadyah; Nurbaiti Nurbaiti (Penerbit Jurnal Indonesia, 2021)
As an Integrated system, ERP is a corporate information system designed to open all the resources, information and activities needed for complete business processes, namely ERP is software that integrates all processes within a company, can unify various components both physically and virtual , such as marketing, finance, production, and human resources. The integration process in business is considered very important for a company, its use through computer-based ERP systems can manage business and improve business performance better. System integration can reduce the trigger for lost or stolen data, using this ERP system can make an integrated process and avoid misuse and companies can unify and observe the pace of their business.